Electron spin resonance studies of the organic superconductor beta"-(BEDT-TTF)(4)[(H3O)Fe(C2O4)(3)]C6H5CN - Narduzzo, A; Ardavan, A; Singleton, J; Pardi, L; Bercu, V; Akutsu-Sato, A; Akutsu, H; Turner, S; Day, R (2004)
We applied magneto-optical techniques to investigate the electron spin resonance (ESR) spectra of single crystal and powder samples of the organic superconductor beta"-(BEDT- TTF)(4)[(H3O)Fe (C2O4)(3)]C6H5CN. Data were obtained in magnetic fields up to 10 Tesla using both cylindrical and rectangular resonators at 55, 63 and 72 GHz and transmission measurements at 95 and 190 GHz with field modulation. Analysis of the high field-high frequency ESR lines for different field orientations and temperatures allows the determination of the g-value anisotropy and the zero-field splitting parameters for the Fe3+ ions (S = 5/2), showing that they occupy a site with distorted octahedral symmetry. The temperature and frequency dependences of the magneto-optical spectra are used to identify the nature of the interaction between localised Fe spins and between the local moments and the delocalised carriers.